API strategy for decision makers - Amundsen, Michael; Gilling, Derric (O'Reilly Media, Inc., 2022)
API Strategy for Decision Makers provides actionable best practices for building winning API products. Whether you're with an API-first company or with an existing enterprise software company looking to expand your API offerings, this report shows you how to grow your API product into a center of revenue and metrics to measure against. Authors Mike Amundsen and Derric Gilling draw on real-life examples to guide you through the important considerations for successfully developing and executing on your API strategy. By identifying winning business cases, sharing best practices for adoption and monetization, and showing you how to create a great API experience, this report presents a detailed overview for every C-suite executive and product owner managing an API platform.